The Relationship Of Maternal Knowledge About Exclusive Breastfeeding With Weight Gain of Infants Aged 0-6 Months in Atikah Midwife Clinic Sipolu-polu Subdistrict, Panyabungan District, Regency Mandailing Christmas In 2023 - Nasution, Helmi Wardah (Cattleya Darmaya Fortuna, 2024)
Breast milk is very important for babies as a natural immune system compared to formula feeding to babies because the development of the baby's digestive system that is not optimal will be at risk of allergies to diarrhea, digestive disorders, constipation and shape. With breastfeeding, its growth and development are more mature compared to formula feeding. Milk contains fats, proteins, whey, casein, carbohydrates, energy, minerals, sodium, potassium, phosphorus, chloride, magnesium and iron. The protein content in breast milk is higher compared to formula milk. A higher casein content in formula milk will form relatively hard clots in the baby's stomach. This study aims to determine the relationship between maternal knowledge about exclusive breastfeeding with weight gain for babies aged 0-6 months at the Atikah Sipolu Midwife Clinic – Polu, Panyabungan District, Mandailing Natal Regency, 2023. The type of research used is descriptive research with a cross sectional approach The population in the study is mothers who have babies 0-6 months in the nuratikah sipolu-polu clinic. The sampling technique uses Total Sampling with a sample size of 40 people. Data collection by using primary and secondary data. Data analysis using the chi -square test with a significant level of p<0.05). The results of the analysis showed that there was a relationship between maternal knowledge about exclusive breastfeeding with weight gain of babies aged 0-6 months with a value of P = 0.032 where P = <0.05. It is hoped that health workers will carry out counseling and counseling activities to increase maternal knowledge about exclusive breastfeeding.